Graphene Oxide/Chitosan/Polyvinyl-Alcohol Composite Sponge as Effective Adsorbent for Dyes - Xu, Xiaoqi (Water environment research : a research publication of the Water Environment Federation, 2017)
Water pollution is one of the most pervasive problems afflicting people. Therefore, seeking highly efficient, low-cost methods to decontaminate water is very much in demand. In this paper, chitosan/polyvinyl-alcohol composite sponges are synthesized via foamed cross-linking method while incorporating different amount of graphene oxide, the resultant graphene oxide/chitosan/polyvinyl-alcohol composite sponges (GCS) are characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared (FTIR), indicating the reasonable dispersion of graphene oxide in the matrix. Furthermore, some physical properties (water absorption, water retention, apparent density, porosity) are also determined; water absorption is high up to 873%, apparent density is lower than 0.25 g/cm3, and porosity could reach 78%. The GCSs also manifest high adsorption ability, as effective adsorbent for Acid Red 37 (AR 37) solution. The relationship between adsorption capacity and independent variables (adsorbent mass, initial dye concentration, and contacting time) is obtained. The optimal adsorption capacity value of AR 37 on GCS could reach 421.5 mg/g